The influence of sleep disturbances on the development of insulin resistance - a literature review - Anna Chmura; Katarzyna Skowrońska; Anna Karaś; Patrycja Baciur; Filip Białas (Journal of Education, Health and Sport, 2022)
Introduction and purpose of the work: Sleep is essential for the proper functioning of the body. Adequate quality and quantity of sleep affects metabolic processes, including glucose metabolism, as well as the sensitivity of tissues to insulin, the reduction of which is called insulin resistance. It leads to an increased production of glucose in order to maintain normal blood glucose levels. Insulin resistance is a modifiable risk factor of, inter alia, type 2 diabetes. The aim of this study is to summarize the current knowledge on the relationship between sleep deprivation and an increased risk of developing insulin resistance.